The surge of RSV and other respiratory viruses among children during the second COVID-19 pandemic winter season - Riepl, Angela; Straßmayr, Lena; Voitl, Peter; Ehlmaier, Paulina; Voitl, Julian J. M.; Langer, Klara; Kuzio, Ulrike; Mühl-Riegler, Alexandra; Mühl, Bernhard; Diesner-Treiber, Susanne C. (Frontiers in Pediatrics, 2023)
Background: The non-pharmaceutical measures in the first Covid-19 winter season significantly impacted respiratory pathogens such as RSV, influenza, or metapneumovirus, which cause respiratory infections, especially in infants and young children. This longitudinal prospective study aimed to determine how less strict measures affect the pathogen profile in the second winter season. Methods: From September 2021 till the end of March 2022, 678 children (0-36 months) admitted to Vienna's largest pediatric center with an acute respiratory infection were enrolled in this study. The researchers performed nasal swabs and tested them by multiplex PCR for 23 respiratory pathogens, chronicled clinical features and treatment, and analyzed the effect of lockdown on the pathogen prevalence. Results: The 815 smears of 678 children revealed the most common pathogens to be rhino-/enterovirus (38.5%), RSV (26.7%), and metapneumovirus (7.2%). The lockdown interrupted the early RSV onset in September (RR 0.367, CI (0.184-0.767), p=0.003), while no effects on the other pathogens were found. Metapneumovirus started circulating in January. Influenza was only sporadically detected. The hospitalization rate was significantly higher than last season due to RSV (OR 4.089, 95%CI (1.414-11.827), p-adj=0.05). Conclusion: With more flexible non-pharmaceutical measures, children aged 0-36 months started presenting again with viral pathogens, such as RSV and metapneumovirus. RSV, associated with a high hospitalization rate, had a very early onset with an abrupt interruption due to the only lockdown.